Analisis Aksesibilitas Spasial Satuan Pelayanan Pemenuhan Gizi (SPPG) di Kota Ambon Menggunakan Pendekatan Isochrone - Adhitya Ferdiansyah Murdiyanto (Prodi PWK Universitas Tadulako, 2026)
The Free Nutritious Meals (MBG) is one of the Indonesian government's programs in realizing Indonesia's golden age by 2045. The results of the study state that the effectiveness of the MBG program is highly dependent on targeted operational governance, considering the still high level of inequality in Indonesia, especially in eastern Indonesia. The purpose of this study is to measure the effectiveness of the SPPG Location in serving educational facilities in Ambon City. In line with that, according to the Decree of the Head of the National Nutrition Agency number 401.1 of 2025 concerning technical guidelines for the Governance of the Implementation of the Free Nutritious Meal Program in 2026, 1 SPPG point has a maximum radius of 6 km or a maximum travel time of 30 minutes. From this basis, the researcher analyzed using the isochrone analysis approach of travel distance, isochrone travel time and time-matrix distance. All data were taken from Google POI taken from Google Maps scraping. The results of the time-matrix distance analysis showed that 67% of educational facilities were in Class 3 (low accessibility) with a travel time of >30 minutes. These findings imply the need to evaluate SPPG placement policies, not only based on air radius but also taking into account road network and topographic analysis. The study's primary recommendation is the implementation of a Hub-and-Spoke strategy by adding sub-distribution points and utilizing motorcycles (refrigerated box motorcycles) to reach geographically challenging areas, such as South Leitimur District, to ensure the nutritional quality of food is maintained until it reaches students.